"Optimización multiobjetivos utilizando mallas variables" - Haro Bustamaante, Naira Génesis (2020)
This research project presents a proposal of multi-objective optimization based on the algorithm of optimization of Mallas Variables (VMO). This proposal will be developed through the study of running that are evolutionary algorithms, of the same one parameters and its operators. It is necessary to stress that the VMO algorithm carry out a phase called clearing by which uses the selection operator, reason why is considered possible the realization of this proposal. Once developed the new multi-objective algorithm test will be realized with multi-objective problems the same ones that are describedfurther on in text. The results obtained will be compared with other algorithms in multi-objective optimization. The VMO multi-objective algorithm was incorporated into Jmetal tool, which was selected by having some optimization algorithms multi-objective and monobjetivo, optimization problems and for being an open source tool. In addition were used some of the main classes of Jmetal tool and others were implemented to obtain a correct running of the algorithm